The Effect of Uncertainty Information on Short-term Reliability in Power Systems. Issue 27 (2016) - Park, Jong-Keun; Choi, Jaeseok; Min, Chang-Gi
Abstract: This paper examines the effect of uncertainty information on short-term reliability using a risk index termed the ramping capability shortage expectation (RSE), which is calculated by adding the probabilities that the ramping capability shortage will occur. The failure rate of generators and the standard deviation of net load forecast error (NLFE) were chosen as the parameters describing the uncertainty information. Markov-chain-based capacity state model was used to describe the generator's state. The NLFE was represented as a normal distribution, which is approximated by a seven-step function. With a modified IEEE-RTS-96, the sensitivity analysis on the uncertainty information was carries out. The sensitive generators with the changes in failure rate were found. The effect of the accuracy of net load forecast on the risk of the system was also identified.